2012
DOI: 10.1371/journal.pone.0038037
|View full text |Cite
|
Sign up to set email alerts
|

A Policy-into-Practice Intervention to Increase the Uptake of Evidence-Based Management of Low Back Pain in Primary Care: A Prospective Cohort Study

Abstract: BackgroundPersistent non-specific low back pain (nsLBP) is poorly understood by the general community, by educators, researchers and health professionals, making effective care problematic. This study evaluated the effectiveness of a policy-into-practice intervention developed for primary care physicians (PCPs).MethodsTo encourage PCPs to adopt practical evidence-based approaches and facilitate time-efficient, integrated management of patients with nsLBP, we developed an interdisciplinary evidence-based, pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 65 publications
(103 reference statements)
2
49
0
Order By: Relevance
“…Other studies have found an association between the GPs and PCPs orientation or beliefs with his/her recommendations and consistency with guidelines, similar to our GK measurement. 10,14,17,29,[30][31] Additional studies also found a connection between RTI and CA&B, 2, 5, 32 an association that was not evident in our results.It is possible that RTI and CA&B are associated in Europe and the U.S. due to the differences in family medicine education among Israel, Europe and the U.S. 33 In order to complete a residency in Family Medicine (FM) in Israel, the student must first complete the sixyear MDprogram, pass a national exam, fulfill a one year rotating internship and finishthe FM residency program. This includes 15 months in primary care teaching clinics, 10 months in the internal medicine department, 5 months in pediatrics, two in Emergency Medicine and four months spent in two month rotations chosen from other specialties including oncology, gastroenterology, etc...…”
mentioning
confidence: 45%
See 1 more Smart Citation
“…Other studies have found an association between the GPs and PCPs orientation or beliefs with his/her recommendations and consistency with guidelines, similar to our GK measurement. 10,14,17,29,[30][31] Additional studies also found a connection between RTI and CA&B, 2, 5, 32 an association that was not evident in our results.It is possible that RTI and CA&B are associated in Europe and the U.S. due to the differences in family medicine education among Israel, Europe and the U.S. 33 In order to complete a residency in Family Medicine (FM) in Israel, the student must first complete the sixyear MDprogram, pass a national exam, fulfill a one year rotating internship and finishthe FM residency program. This includes 15 months in primary care teaching clinics, 10 months in the internal medicine department, 5 months in pediatrics, two in Emergency Medicine and four months spent in two month rotations chosen from other specialties including oncology, gastroenterology, etc...…”
mentioning
confidence: 45%
“…This has been done successfully in specific populations with training sessions, courses, printed educational material, and media campaigns. 4,9,[15][16][17][18] Another practitioner related factor which may pose a challenge to LBP guideline implementation may be the PCPs' readiness-to-change their practice behavior. If PCPs are familiar with the recommended LBP guidelines, but lack a willingness to change their management of LBP patients, then dissemination of guidelines will be ineffective.…”
mentioning
confidence: 99%
“…Further, although the wait to access pain medicine services in Australia has been protracted for consumers, 17 timely access has been dramatically improved in WA owing to the introduction of a system-oriented MoC for pain services, 18 introduced in parallel with initiatives to build workforce and consumer capacity to better manage musculoskeletal pain syndromes. [19][20][21][22][23] A recent audit in WA identified positive uptake of all disease-group MoCs across the WA Health Services, particularly with respect to awareness and service planning, yet responders identified that sustainable implementation efforts were stymied by lack of resources to sustainably support implementation efforts. 24 In this regard, long-term sustainability and impact of MoCs will be dependent on their uptake and support by middle and senior health managers and policy makers and research providing evidence of their benefit for improving health outcomes and system efficiencies.…”
Section: Models Of Care: Do They Make a Difference?mentioning
confidence: 99%
“…Scott et al (2010) conducted a systematic review on 14 studies published in Europe, Canada and the USA with the aim to identify the so called 'know-do' gap in primary care setting [23]. The know-do gap refers to the discrepancy between management advised by the guideline and management executed in clinical practice [23,24]. Evidence of the existence of this know-do gap among physicians and physiotherapists could be seen in the choice of treatments strategies.…”
Section: Satisfaction With Treatment and Consultation Time (N=311)mentioning
confidence: 99%
“…A more thorough screening for yellow flags should be done at first consultation, after which the LBP patient, according to the phase of recovery he is in, can be appropriately referred. CHC staff should receive training to improve their knowledge of LBP and risk factors for chronicity [24]. Within the current shift taking place in South African CHCs towards a patient-centered perspective, attention should be given to improving patients' health literacy.…”
Section: Satisfaction With Treatment and Consultation Time (N=311)mentioning
confidence: 99%